Mobile eye services: Literature review with special reference to the experience of Al-Basar International Foundation - Adel A Rushood (Wolters Kluwer Medknow Publications, 2010)
Purpose: To evaluate the concept of quality assured mobile eye services (MES) in implementing the vision 2020 initiative. Materials and Methods: Literature review as well as the medical records of Al-Basar International Foundation (BIF) on MES. Emphasis was focused on the causes of blindness, objectives, operation, management and the benefits of MES, a critical appraisal of MES, training for MES and the relationship with other organizations and concerned government agencies. Findings: More than 38 countries have been included in this exercise during which more than 620 eye camps have been conducted. More than two million people have benefited from the services provided including medicines and glasses in these eye camps and about 180,000 sight restoring surgeries performed for cataract, glaucoma etc. Conclusion: Quality assured MES are a very important means of tackling the problems of blindness and implementing the vision 2020 initiative. The adoption of this concept by major stake-holders in the prevention of blindness (e.g. WHO, IAPB) will bring an additional momentum to the achievement of this noble goal.